The Relationship between Training, Employee Attitude, Management Commitment and Safety and Health Awareness: A Study Among Workers in SIRIM Berhad - Chahel, Ashweena Kaur; Ismail, Siti Norziah (Research in Management of Technology and Business, 2025)
The study investigates the relationship between training, employee attitude, management commitment, and safety and health awareness among workers in SIRIM Berhad, Shah Alam. The research aims to increase safety and health awareness among employees and contribute to a better understanding of training, employee attitude, and management commitment at SIRIM Berhad. The study uses a quantitative research design and focuses on a limited population of 1656 employees from four departments within the company. The research methodology involves a cross-sectional survey design, data collection through questionnaires, and data analysis using SPSS software. The study’s objectives include determining the level of safety and health awareness, identifying the relationships between training, employee attitude, and management commitment, and providing suggestions for future work. Quantitative study had been used in the study.This study also used convenience sampling. An online survey has been conducted among 310 employees in SIRIM Berhad Shah Alam, Malaysia with a response rate of 100%. Data were analyzed using descriptive analysis and Spearman’s correlation analysis.This study found that the level of safety and health awareness is high. Training, employee attitude and management commitment had a significant relationship with safety and health awareness.